KONTRIBUSI DAN EFEKTIVITAS PENERIMAAN PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA GORONTALO - Makausi, Alma Meita; Sabijono, Harijanto; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Parking Tax is a regional tax which can also affect the increase of local revenue. Effectiveness and contribution of Parking Tax is one tool to measure the extent of Local Government achievement in collecting Parking Tax contributes to the region?s original revenue is very important to develop a region. This study aims to (1) find out the percentage level of effectiveness of Parking Tax in Gorontalo City (2) find out how much the percentage of Parking tax revenue contribution to the Original Revenue of Gorontalo City. This study applies a descriptive qualitative analysis method. The result of research obtained by the Gorontalo City parking tax in 2014-2018 experienced a fluctuation with an average percentage of 84,95%  entered the criteria quite effectively, and the parking tax in Gorontalo City contributed less to the orginal regional income because it had an average percentage of 0,06% of revenue from the Gorontalo City original income.